Bubble Ticket Trip: Exploring the Mechanism of miRNA Sorting into Exosomes and Maintaining the Stability of Tumor Microenvironment - Wang L; Liu H; Chen G; Wu Q; Xu S; Zhou Q; Zhao Y; Wang Q; Yan T; Cheng X (International Journal of Nanomedicine)
Lu Wang, Huijuan Liu, Guohui Chen, Qinglu Wu, Songrui Xu, Qichao Zhou, Yadong Zhao, Qiaorong Wang, Ting Yan, Xiaolong Cheng Key Laboratory of Cellular Physiology of the Ministry of Education, & Department of Pathology, Shanxi Medical University, Taiyuan, Shanxi Province, 030001, People’s Republic of ChinaCorrespondence: Ting Yan; Xiaolong Cheng, Email enntei@hotmail.com; chengxl@sxmu.edu.cnAbstract: Exosomes are vesicles ranging from 30 to 100 nanometers in size that show great potential as carriers for therapeutic uses and drug delivery. Enriching a specific set of miRNAs in exosomes emphasizes the existence of particular sorting mechanisms that manage the targeted cargo packaging. The molecular mechanism for miRNA sorting has not been understood. It is crucial to understand the mechanism of exosome encapsulation to develop its therapeutic potential. In this review, we will explore the particular processes through which exosomes naturally encapsulate miRNA, as well as discuss the effect on tumors after encapsulation of miRNAs. We also summarize the effects of targeted drug delivery using genetic engineering and chemical methods to modify exosome-encapsulated miRNA. Finally, gaining insight into how exosome cargo is sorted could be applied in clinical settings for precise drug delivery and to hinder the progression of diseases.Keywords: exosomes miRNA, sorting mechanism, tumor microenvironment, cancer